2021
DOI: 10.1021/acsami.0c17943
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Atomic Layer Deposition of Gold: Mechanistic Insights, Nucleation, and Epitaxy

Abstract: An in situ microbalance and infrared spectroscopic study of alternating exposures to Me2Au­(S2CNEt2) and ozone illuminates the organometallic chemistry that allows for the thermal atomic layer deposition (ALD) of gold. In situ quartz crystal microbalance (QCM) studies resolve the nucleation delay and island growth of Au on a freshly prepared aluminum oxide surface with single cycle resolution, revealing inhibition for 40 cycles prior to slow nucleation and film coalescence that extends over 300 cycles. In situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…plays an important role in the Au nucleation inhibition from the first-principles computations and in situ infrared spectroscopy. 19 The ALD reaction mechanisms of TiCl 4 , 20 (DFT) and thermodynamic calculations, and the surface termination plays an important role in the nucleation delay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…plays an important role in the Au nucleation inhibition from the first-principles computations and in situ infrared spectroscopy. 19 The ALD reaction mechanisms of TiCl 4 , 20 (DFT) and thermodynamic calculations, and the surface termination plays an important role in the nucleation delay.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been devoted to study the mechanism of ALD nucleation delay by performing theoretical simulation methods assisted in situ charaterizations. Hock et al resolve the nucleation delay and island growth of thermal ALD of gold on aluminum oxide by in situ quartz crystal microbalance, and it is found that surface chemistry (including the intermediates, volatile byproducts, etc.) plays an important role in the Au nucleation inhibition from the first-principles computations and in situ infrared spectroscopy . The ALD reaction mechanisms of TiCl 4 , CoCp 2 , and RuCp 2 on SiO 2 surfaces have been investigated by density functional theory (DFT) and thermodynamic calculations, and the surface termination plays an important role in the nucleation delay.…”
Section: Introductionmentioning
confidence: 99%